2022
DOI: 10.1093/brain/awac379
|View full text |Cite
|
Sign up to set email alerts
|

Venglustat combined with imiglucerase for neurological disease in adults with Gaucher disease type 3: the LEAP trial

Abstract: Gaucher disease type 3 (GD3) is a chronic neuronopathic disorder with wide-ranging effects, including hepatosplenomegaly, anaemia, thrombocytopenia, skeletal disease, and diverse neurological manifestations. Biallelic mutations in GBA1 reduce lysosomal acid β-glucosidase activity, and its substrates, glucosylceramide and glucosylsphingosine, accumulate. Enzyme replacement therapy (ERT) and substrate reduction therapy (SRT) ameliorate systemic features of Gaucher disease, but no therapies are approved for neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 71 publications
1
29
0
3
Order By: Relevance
“…8 GD type 3 (chronic neuronopathic), is a subacute neurological form with a slower progression of neurological symptoms and later onset of the disease. 9 The diagnosis of GD is often accompanied by delays because its diagnosis requires the use of invasive and resource-intensive procedures, such as pathological biopsies, molecular genetic tests, and enzyme activity assays. 10 A multidisciplinary combination of internal medicine, paediatrics, radiology, pathology, and molecular biology is beneficial in the treatment of GD.…”
Section: Discussionmentioning
confidence: 99%
“…8 GD type 3 (chronic neuronopathic), is a subacute neurological form with a slower progression of neurological symptoms and later onset of the disease. 9 The diagnosis of GD is often accompanied by delays because its diagnosis requires the use of invasive and resource-intensive procedures, such as pathological biopsies, molecular genetic tests, and enzyme activity assays. 10 A multidisciplinary combination of internal medicine, paediatrics, radiology, pathology, and molecular biology is beneficial in the treatment of GD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors of the study do not recommend an off-label use of the compound outside clinical studies. [128] Finally, in a recent study Venglustat, beside its ability to inhibit the activity of GCS, has been shown to competitively bind at the N-terminal methyltransferase 1 (NTMT1) substrate binding site, displaying an IC 50 value of 0.5 μM in both biochemical and cellular inhibition assays. Therefore, it has been selected as lead compound for the development of novel inhibitors of NTMT1 which has physiopathological implications in neurogenesis, retinoblastoma and cervical cancer.…”
Section: Venglustat (Ibiglustat or Enz-682452 Or Gz-161)mentioning
confidence: 99%
“…In addition, amelioration of ataxia and neurocognitive deficits in GD3 patients have been observed. However, the authors of the study do not recommend an off‐label use of the compound outside clinical studies [128] …”
Section: Substrate Reduction Therapymentioning
confidence: 99%
“…Of the LSDs, Gaucher disease (GD) has received particular attention over the past 15 years or so due to the genetic association between mutations in GBA, which encodes the defective lysosomal enzyme in GD, acid-beta-glucosidase (GCase), and Parkinson's disease (PD) 3 , although little data is available to permit delineation of the cellular and biochemical basis of this association 4 . GD is typically divided into three clinical subtypes, with the juvenile neurological form (type 3) the target of novel forms of therapeutic intervention, such as substrate reduction therapy which partially inhibits synthesis of the accumulating substrate 5 .…”
Section: Introductionmentioning
confidence: 99%